2014
DOI: 10.1007/s13762-014-0499-x
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of azo dyes by anaerobic–aerobic sequential biological treatment: a review

Abstract: Dyes are synthetic organic compounds widely used in various industries such as, textile, leather, plastic, food, pharmaceutical, and paints manufacturing industries. Coloured effluents are highly toxic to the aquatic life and mutagenic to humans. Wastewater containing dyes has become an important issue demanding serious attention. Among the synthetic dyes, azo dyes are the largest and most widely used dyes and account for more than half of the annually produced dyes. The biodegradation of azo dyes is difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(91 citation statements)
references
References 83 publications
(118 reference statements)
3
83
0
2
Order By: Relevance
“…According to Frijters et al (2006), it was almost impossible to quantify the dye concentrations and know its exact composition at a given time due to the diversity of organic compounds present. However, since the largest group (60-70 %) of synthetic colorants is considered azo dyes (Isik and Sponza 2006;Popli and Patel 2015), it is still possible that such chromophores as azo group (-N=N-) can be broken down into more easily biodegradable compounds during the anaerobic step, then to be further mineralized in the subsequent aerobic step. The exact mechanism for the dye reduction, whether occurring intracellularly or extracellularly, is still a subject of investigation (Shah 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Frijters et al (2006), it was almost impossible to quantify the dye concentrations and know its exact composition at a given time due to the diversity of organic compounds present. However, since the largest group (60-70 %) of synthetic colorants is considered azo dyes (Isik and Sponza 2006;Popli and Patel 2015), it is still possible that such chromophores as azo group (-N=N-) can be broken down into more easily biodegradable compounds during the anaerobic step, then to be further mineralized in the subsequent aerobic step. The exact mechanism for the dye reduction, whether occurring intracellularly or extracellularly, is still a subject of investigation (Shah 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Physical and chemical treatment systems such as coagulation/sedimentation, Fenton oxidation, and ozone oxidation suffer from some drawbacks, including the requirement of intensive energy and supplementary chemicals, the high cost, and the formation of hazardous by-products (Hong et al 2013;Fan et al 2014). Biological treatment, in comparison, may be a good alternative due to the lower operational cost compared to most physicochemical technologies and the eco-friendly features (Popli and Patel 2015), despite such shortcomings as sludge bulking and low treatment efficiency for refractory compounds (Ahn et al 1999). Li and Zhao (1997) reported that biological processes applied in the treatment of textile wastewater showed a practical limit in terms of the removal of organics, color, and other biodegradable substances in different activated sludge processes, with the elimination efficiencies of 90 % for biochemical oxygen demand (BOD), 40-50 % for chemical oxygen demand (COD), and 20-30 % for color.…”
Section: Introductionmentioning
confidence: 99%
“…Azo dyes, which are aromatic compounds with one or more -N=N-groups, are the most common synthetic dyestuffs released to the environment via textile industries [4]. Anionic dyes for polyamide and protein substrates are known as acid dyes.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] and (ii) by means of biodegradation methods such as activated sludge, and UASB [3][4][5][6]. During conventional aerobic wastewater treatment, azo dyes are not degraded.…”
mentioning
confidence: 99%
“…During conventional aerobic wastewater treatment, azo dyes are not degraded. On the other hand, azo linkages are easily reduced under anaerobic condition with digester sludge, anaerobic granular sludge and sediments [5][6][7]. The reduction of azo dyes results in the formation of aromatic amines.…”
mentioning
confidence: 99%